Myricetin bioactive effects: moving from preclinical evidence to potential clinical applications - Yasaman Taheri; Hafiz Ansar Rasul Suleria; Natália Martins; Oksana Sytar; Ahmet Beyatli; Balakyz Yeskaliyeva; Gulnaz Seitimova; Bahare Salehi; Prabhakar Semwal; Sakshi Painuli; Anuj Kumar; Elena Azzini; et al. (BMC, 2020)
Abstract Several flavonoids have been recognized as nutraceuticals, and myricetin is a good example. Myricetin is commonly found in plants and their antimicrobial and antioxidant activities is well demonstrated. One of its beneficial biological effects is the neuroprotective activity, showing preclinical activities on Alzheimer, Parkinson, and Huntington diseases, and even in amyotrophic lateral sclerosis. Also, myricetin has revealed other biological activities, among them as antidiabetic, anticancer, immunomodulatory, cardiovascular, analgesic and antihypertensive. However, few clinical trials have been performed using myricetin as nutraceutical. Thus, this review provides new insights on myricetin preclinical pharmacological activities, and role in selected clinical trials.